Evaluation of the functioning of patients with diabetic foot syndrome - Ponczek, Danuta; Bąk, Agata (Pielęgniarstwo w Opiece Długoterminowej / Long-Term Care Nursing, 2019)
Abstract Diabetes is a chronic disease leading to many complications. One of them is the diabetic foot syndrome (DFS) that disturbs the patient’s functioning in every sphere of life. Aim of the study The evaluation of the functioning of patients with the diabetic foot syndrome. Material and methods The study was conducted among 68 patients with DFS treated in the Outpatient Department of Chronic Wounds and in the Department of Vascular Surgery and Angiology at Antoni Juras z University Hospital No. 1 in Bydgoszcz. Interview, palpation, observation and author’s questionnaire, PEDIS classification and Barthel scale were used in order to achieve the goals of the study. Results The study evaluated physical condition of the patients with DFS by using the Barthel scale. Their condition turned out to be “light”. Better dexterity was observed among patients without the need of hospitalization during the year before the interview and among those people who were in a relationship. Patients func¬tioned on the average level in the mental and social sphere. The worse mood was more frequently observed among women. People that suffered from diabetes for a shorter time and men in general were more active in the social sphere. Conclusions DFS causes disorders in allthree spheres of the patient’s life. It is advisable to provide patients with the spe¬cialist care by an interdisciplinary team that will increase the overall quality of life for patients with DFS.